2019
DOI: 10.2147/vhrm.s226009
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Long-Term Allopurinol Therapy on Left Ventricular Mass Index in Patients with Ischemic Heart Disease; A Cross-Sectional Study</p>

Abstract: BackgroundLeft ventricular hypertrophy (LVH), as assessed by measurement of left ventricular mass (LVM), is one of the most important cardiovascular risk factors. It is commonly present in patients with ischemic heart disease (IHD), irrespective of the level of blood pressure; recently, oxidative stress has been shown to be an important factor in its development. The question then arises: can this risk factor be modified by antioxidant treatment (e.g., with allopurinol, a xanthine oxidase inhibitor)?MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…These comorbidities, along with beta-blockers and diuretics, are known to have negative effects on glucose homeostasis [ 32 ], raising the possibility of an otherwise greater beneficial effect from allopurinol. In that regard, the magnitude of drop in HbA1c in this study was smaller than was observed in another sample of our population in a previous study of similar sample size, allopurinol dose and duration (−0.8% reduction) [ 22 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…These comorbidities, along with beta-blockers and diuretics, are known to have negative effects on glucose homeostasis [ 32 ], raising the possibility of an otherwise greater beneficial effect from allopurinol. In that regard, the magnitude of drop in HbA1c in this study was smaller than was observed in another sample of our population in a previous study of similar sample size, allopurinol dose and duration (−0.8% reduction) [ 22 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Using previous results [ 22 ], and assuming a pooled standard deviation of 2.05 units, the study would require a sample size of 89 patients in each group (a total sample size of 178 patients) to achieve a 90% power and a level of significance of 5% (two-sided), to detect a true difference of 1% in glycated hemoglobin means between allopurinol users, and control subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment of eligible patients in both studies was described elsewhere. 10 , 11 The variables collected were: patient’s demographic information, NYHA functional class, etiology of heart failure, and co-morbidities (systemic hypertension, diabetes mellitus (DM), dyslipidemia, arrhythmias (including atrial fibrillation (AF)), transient ischemic attacks (TIA), and stroke. Patients’ cardiac medications, anti-diabetic drugs and other relevant drugs were also documented.…”
Section: Methodsmentioning
confidence: 99%
“…Using our previous results (22), and assuming a pooled standard deviation of 2.05 units, the study would require a sample size of 89 patients in each group (a total sample size of 178 patients) to achieve a 90% power and a level of signi cance of 5% (two-sided), to detect a true difference of 1% in glycated hemoglobin means between allopurinol users, and control subjects.…”
Section: Sample Sizementioning
confidence: 99%